Interactions Between Sendai Virus and Human Erythrocytes - Howe, Calderon (1969)
Concentrated Sendai virus, when adsorbed to erythrocytes at 4 C, caused invaginations in the plasma membrane. Following elevation of the temperature to 37 C, the plasma membrane became fused with the viral envelope before dissolution of the virions and rupture of the cells. Cell lysis was accompanied by rapid and total loss of hemoglobin to the extracellular space. Following aqueous pyridine extraction, the hemoglobin-free ghosts remaining were found to be devoid of N-acetylneuraminic acid and to have solubility properties different from those of normal erythrocyte ghosts. By the action of viral neuraminidase, bound N-acetylneuraminic acid was also liberated from purified virus receptor substance whose electrophoretic mobility was thereby substantially reduced. Cu(++) selectively inhibited hemolysis and neuraminidase without interfering with hemagglutination and attachment. Neuraminidase appeared to be essential for Sendai virus hemolysis; viral particle size may also be a critical factor in this process.